Possibilities for the incorporation of African indigenous procedures and mechanisms of dispute resolution in the administration of criminal justice in Nigeria - Salihu, Habeeb Abdulrauf (Contemporary justice review, 2020)
The pre-colonial African communities were ethnically and culturally diverse with no single dominant ethnic and religious group. Unwritten customary law and procedures were the means by which local communities resolved disputes in the absence of state authority. The laws were based on a common cultural belief and ethical codes that generate a binding regulation on members. Communities adopted this model to impose sanctions against violators and resolve disputes arising among members through various mechanisms. However, the introduction of a new justice system by the colonialists completely interrupted the indigenous system. Today, the indigenous justice system in many African countries is restricted to handling only civil matters through the application of ADR to address some of the challenges facing the contemporary justice system. This paper argues that the customary justice procedure can be adopted in criminal matters as a model that seeks to understand and address the realities of the social causes of crime. The paper concludes that the two systems of justice can complement each other to restore public confidence in the system by catering for the loss suffered by victims rather than focusing on the offenders and offence, bringing justice closer to people without any stress, reintegrating offenders back into the society and ensuring social harmony.